Ethylene glycol assisted low-temperature synthesis of boron carbide powder from borate citrate precursors - Rafi-ud-din; G.H. Zahid; Z. Asghar; Muhammad Maqbool; Ejaz Ahmad; Tanvir Azhar; Tayyab Subhani; M. Shahzad (Journal of Asian Ceramic Societies, 2014)
B4C powders were synthesized by carbothermal reduction of ethylene glycol (EG) added borate citrate precursors, and effects of EG additions (0–50 mol% based on citric acid) on the morphologies and yields of synthesized B4C powders were investigated. The conditions most suitable for the preparation of precursor were optimized and optimum temperature for precursor formation was 650 °C. EG additions facilitated low-temperature synthesis of B4C at 1350 °C, which was around 100–300 °C lower temperature compared to that without EG additions. The lowering of synthesis temperature was ascribed to the enlargement of interfacial area caused by superior homogeneity and dispersibility of precursors enabling the diffusion of reacting species facile. The 20% EG addition was optimal with free residual carbon lowered to 4%. For smaller EG additions, the polyhedral and rod-like particles of synthesized product co-existed. With higher EG additions, the morphology of synthesized product was transformed into needle and blade-like structure.